From Moral Threshold to Measurable Parameter, Reconstruction of Extremely Unjust Law (Gustav Radbruch) Through the Layered Justice Index - Ulhaq Ulhaq; Isis Ikhwansyah; Tri Handayani (Journal of Law and Social Politics, 2026)
Background: Modern law reveals a persistent tension between legal certainty and justice, particularly when positive law legitimizes outcomes that contradict human values, as illustrated by Indonesia’s insolvency law practice. Gustav Radbruch’s three fundamental values of law and the Radbruch Formula remain relevant for assessing the limits of validity of positive law. Objective: This study analyzes Radbruch’s conceptual framework of law’s three fundamental values, examines the function of the Radbruch Formula in determining legal validity, and formulates operational parameters for extremely unjust law. Methods: This research employs a normative legal method with a descriptive-analytical approach through library research, drawing on primary, secondary, and tertiary legal materials. Data were collected through document analysis and analyzed qualitatively to synthesize concepts into parameters for identifying extremely unjust law. Results: The results show that law reaching an extreme level of injustice loses its normative legitimacy and binding force; therefore, justice must take precedence over legal certainty in such cases. Indicators include human rights violations, systematic discrimination, denial of due process, inconsistency with constitutional principles, and violations of proportionality, operationalized through the Layered Justice Index as a systematic tool for measuring legal injustice. Conclusion: This research bridges Radbruch’s theory with contemporary legal practice, offering policymakers and judges a measurable, human-value oriented framework for assessing legal validity.